Global climate policy impacts on livestock, land use, livelihoods, and food security - Golub, Alla A.; Henderson, Benjamin B.; Hertel, Thomas W.; Gerber, Pierre J.; Rose, Steven K.; Sohngen, Brent (Proceedings of the National Academy of Sciences - PNAS, 2013)
Recent research has shed light on the cost-effective contribution that agriculture can make to global greenhouse gas abatement; however, the resulting impacts on agricultural production, producer livelihoods, and food security remain largely unexplored. This paper provides an integrated assessment of the linkages between land-based climate policies, development, and food security, with a particular emphasis on abatement opportunities and impacts in the livestock sector. Targeting Annex I countries and exempting non-Annex I countries from land-based carbon policies on equity or food security grounds may result in significant leakage rates for livestock production and agriculture as a whole. We find that such leakage can be eliminated by supplying forest carbon sequestration incentives to non-Annex I countries. Furthermore, substantial additional global agricultural abatement can be attained by extending a greenhouse gas emissions tax to non-Annex I agricultural producers, while compensating them for their additional tax expenses. Because of their relatively large emissions intensities and limited abatement possibilities, ruminant meat producers face the greatest market adjustments to land-based climate policies. We also evaluate the impacts of climate policies on livelihoods and food consumption in developing countries. In the absence of non-Annex I abatement policies, these impacts are modest. However, strong income and food consumption impacts surface because of higher food costs after forest carbon sequestration is promoted at a global scale. Food consumption among unskilled labor households falls but rises for the representative farm households, because global agricultural supplies are restricted and farm prices rise sharply in the face of inelastic food demands.